2020
DOI: 10.13045/jar.2019.00353
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in Pharmacopuncture Treatment for Lateral Epicondylitis

Abstract: The aim of this study was to examine pharmacopuncture treatment for lateral epicondylitis, and to contribute to developing a standardized treatment regimen by reviewing trends in clinical trials. Five randomized controlled trials, 1 case-control study, and 8 cohort studies published after 1999, that involved pharmacopuncture for lateral epicondylitis, were selected from Korean and international online databases (n = 8). The type of pharmacopuncture, dose, frequency, efficacy, and adverse events were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[ 19 , 20 ] It has also been effectively used in the treatment of lateral epicondylitis, acupuncture, [ 27 ] and pharmacopuncture. [ 28 ] There was also a previous study reporting that acupotomy showed a lower rate of recurrence than that in corticosteroid injections for the treatment of tennis elbow. [ 29 ] In the same context, ultrasound-guidance has been actively utilized to enable the administration of minimally invasive percutaneous needle puncture when injecting for the treatment of lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 95%
“…[ 19 , 20 ] It has also been effectively used in the treatment of lateral epicondylitis, acupuncture, [ 27 ] and pharmacopuncture. [ 28 ] There was also a previous study reporting that acupotomy showed a lower rate of recurrence than that in corticosteroid injections for the treatment of tennis elbow. [ 29 ] In the same context, ultrasound-guidance has been actively utilized to enable the administration of minimally invasive percutaneous needle puncture when injecting for the treatment of lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 95%